Perlindungan Hukum Kepemilikan Data Kependudukan di Indonesia Dalam Perspektif Teori Pembentukan Peraturan Perundang-Undangan - Ana Aniza Karunia; Mohammad Jamin (KRTHA BHAYANGKARA, 2023)
The research evaluates the legal protection regulation for the ownership of population data in Indonesia. The type of the research is normative research with statute approaches. This study uses the Theory of Legal Protection, Theory of Legal Certainty, and Theory of Formation of Legislation. The source of research data is secondary data. Data collection technique is documentation study. The use of logic in legal research is deductive logic. The qualitative techniques used is a systematic or logical interpretation technique. The result show that that regulations have not been able to provide legal protection for the ownership of population data in Indonesia because a) the protection of ownership of population data in Indonesia has not been regulated in general regulations, b) Protection of population data ownership in the form of a prohibition is regulated by sectoral regulations. However, it has not regulated in detail how the form of protection of population data about the processing of population data, and isn’t in accordance with the principles of establishing regulations, c) the protection of population data has not been accommodated in various regulations governing the protection of personal data where these regulations are still not in accordance with the principles and principles of establishing regulations.